Effectiveness of Implementation of Siskeudes And Financial Reports of Village Funds in Rejang Lebong Regency - Dwi Sinta; Gayatri Gayatri (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
This research was conducted in Rejang Regency which aims to see how effective the application of village financial information system to village fund financial statements. This research is useful as an evaluation material for local governments in placing human resources engaged in financial management on the other hand information systems help operators in making financial reporting effectively, appropriately and financial reporting in accordance with village government accounting standards. The method used is a simple regression method with the retrieval of questionnaire sampel with predefined criteria. From the results of the dissemination of questionnaire data that can be processed as many as 67 questionnaires. The results of a simple regression test in the study with a value of F count 19,833 with a significance level of 0.000 < 0.005 means that in the study can be used to predict the variable effectiveness of the implementation of siskeudes and financial statements of village funds in other words, namely the implementation of the Village Financial Information System on the financial statements of village funds in an effective manner. Korelasi of 0.484 and coefficient of determination (Rsquare) of 0.243 can be concluded the influence of variable effectiveness of the implementation of siskeudesn on the financial report of village funds by 24.4%.